Narrativa textual: uma análise da produção escrita de crianças que experienciaram o método Montessoriano na Educação Infantil - Lopes, Cristiane de Ávila (2013)
This study describes, analyzes and compares the quality of oral and written narratives produced by two groups of first and second graders. Tolchinsky s four discursive categories (1995) were applied to the analysis: i) the relation among the events and what is said ii) the presence and the absence of the narrator; iii) the actions of the characters and their motivation; and iv) the events and their interpretation, as well as the size and variety of vocabulary. The first group (G1) comprised children that had undergone the Montessori Pedagogy in Pre-school and had experienced activities which aimed at oral and written language. The second group (G2) consisted of children who had neither had contact with such methodology nor taken part in activities which aimed at language practice. Data on oral and written narratives were collected in workshops in which oral and written narratives were produced whereas data on vocabulary were collected by a test that was exclusively designed for the research. Firstly, based on Tolchinsky s discursive characteristics, the description and the analysis of the data on narratives were carried out (first category of analysis). Afterwards, the data on vocabulary (second category of analysis) were analyzed. Results of both groups were then statistically compared. Besides, results of the categories of analysis were discussed and correlated. Results showed that the group that had undergone the Montessori methodology in Pre-school had better results in the categories under analysis. A positive correlation was also established between the children s performance in the discursive categories and the one in the vocabulary tests, both in terms of size and variety. When the results of oral narratives were compared with written ones, the former had higher quality, in both groups, G1 and G2. Furthermore, this study showed that the quality of the narratives is prone to be improved and intensified as children get older and advance in their schooling processes. Finally, the fact that the group whose teaching model is the Montessori one performed better may be related to the kind of tasks the children had to carry out, mainly the ones which aimed at working on oral and written language.